Revisiting the linkage between oil and agricultural commodity prices: Panel evidence from an Agrarian state - Gokmenoglu, Korhan K.; Gungor, Hasan; Bekun, Festus Victor (Wiley, 2021)
This paper utilizes panel methods to consider the dynamic relationship between oil and agricultural commodity prices. The study makes use of monthly measures realized data for six agricultural commodity prices, including cocoa, coffee, wheat, palm oil, soybeans, beef and crude oil. The dataset spans the period 2006-2015 and includes a measure for the effective exchange rate. The results of a panel unit root test suggest that all the variables are stationary after taking the first difference. The Fisher/Johansen cointegration test is then used to suggest that the dataset includes a single cointegrating vector. A regression on the long-run characteristics of the data is then used to show that crude oil prices are positively correlated to agricultural commodity prices. This suggests that oil price for the case of Nigeria drives demand for agricultural crop commodity. The results show that agricultural commodity prices in Nigeria are responsive to global oil prices. The subsequent causality test that account for heterogeneity tests performed on the first difference of the variables reject the null hypothesis of no Granger causality in either direction between crude oil prices and agricultural crop commodity. This suggests that oil prices drive agricultural commodity prices and vice versa. Based on these outcomes several policy directions were rendered in concluding section.
Keywords: agricultural commodity; Nigeria; oil prices; panel data econometrics